The Spillover Effects of the Digital Economy - Evgeniya K. KARPUNINA; Natalia N. GUBERNATOROVA; Amira A. DAUDOVA; Zarema N. STASH; Larisa A. KARGINA (Communications of International Proceedings, 2020)
The research is aimed at identifying the specifics of spillover effects that occur in the economic system in the process of digital development, as well as developing conceptual principles for their assessment. The authors attributed the direct effect of investing in digitalization to the growth of the digital economy's share in GDP, increased labor productivity, expanded market volumes and additional profit, and increased exports of ICT products. The authors adapted the concept of the “spillover effect” to research on the digital economy. The authors revealed the specifics and systematized the spillover effects of the digital economy (spillover-the effect of changes in the labor market and employment, spillover-the effect of social and regional asymmetry in the use of digital technologies, spillover-the effects of information risks), and justified their positive and negative impact on the national economy. The analysis of approaches to evaluating spillover effects allowed the authors to formulate recommendations for their evaluation based on the statistical method of variance and mean square deviation.
Keywords: spillover effects; digital economy; labor market; unemployment; digital inequality; digital gaps; information risks; social and regional asymmetry